Design and Testing of Digital Microfluidic Biochips - Zhao, Yang. (Springer New York : Imprint: Springer, 2013)
This book provides a comprehensive methodology for automated design, test and diagnosis, and use of robust, low-cost, and manufacturable digital microfluidic systems. It focuses on the development of a comprehensive CAD optimization framework for digital microfluidic biochips that unifies different design problems. With the increase in system complexity and integration levels, biochip designers can utilize the design methods described in this book to evaluate different design alternatives, and carry out design-space exploration to obtain the best design point. Describes practical design automation tools that address different design problems (e.g., synthesis, droplet routing, control-pin mapping, testing and diagnosis, and error recovery) in a unified manner; Applies test pattern generation and error-recovery techniques for digital microfluidics-based biochips; Uses real bioassays as evaluation examples, e.g., multiplexed in vitro human physiological fluids diagnostics, PCR, protein crystallization.